2011
DOI: 10.1111/j.1741-2358.2011.00552.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of temporomandibular joint disorder in older patients by magnetic resonance imaging

Abstract: Study of temporomandibular joint disorder in older patients by magnetic resonance imaging (MRI)Objectives: To compare characteristics in older patients in a sample of the general population of those with temporomandibular joint disorder (TMJD). Materials and methods: A prospective study was carried out between 2001 and 2008 in patients with TMJD. The whole sample consisted of 141 patients divided in two groups: 31 patients aged over 60 (median age 67.9, ranging from 60 to 82) and the remaining 110 patients (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Headache was a symptom closely related to TMDs, with half of the elderly Vietnamese studied suffering from headaches. This result was higher than a study conducted in Brazil (38.5%), 1 lower than another in Croatia (61.2%), 14 but in line with a finding in Hong Kong (52.6%). 12 Previous studies have reported that headaches are more common in females than males, 10,22 which is also consistent with our study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Headache was a symptom closely related to TMDs, with half of the elderly Vietnamese studied suffering from headaches. This result was higher than a study conducted in Brazil (38.5%), 1 lower than another in Croatia (61.2%), 14 but in line with a finding in Hong Kong (52.6%). 12 Previous studies have reported that headaches are more common in females than males, 10,22 which is also consistent with our study.…”
Section: Discussionsupporting
confidence: 78%
“…3,8 Clicking and crepitus of the temporomandibular joint (TMJ) were found in 25% of an elderly population aged 60–80 years old; 3 restricted mandibular range of motion has been significantly associated with aging; masticatory muscle tenderness also causes a decline in oral health among the elderly. 3,8,12,14,15 Moreover, the elderly are most vulnerable to tooth loss and alteration to functional occlusion, which are known risk factors of TMD. 10,16,17 A shortened dental arch due to missing teeth decreases masticatory function and is attributed to muscle tenderness.…”
Section: Introductionmentioning
confidence: 99%
“…However, some of the discs were significantly more anterior and had abnormal shape and therefore constitute a subgroup that should be followed prospectively. Degrees of anteriorly located discs in normals is described on MRIs in 20–34% and is considered a variant of normal in those cross‐sectional studies. Disc positions up to +15 degrees on medial tomograms and +30 degrees on lateral tomograms have been regarded as normal variations .…”
Section: Does Condyle–fossa Position Define the Disc Shape?mentioning
confidence: 99%
“…However, awareness of such symptoms tends to decrease with age (2). Badel et al classified patients as older (≥ 60 years) and younger (< 60 years) and noted a high level of anxiety in both patient groups, regardless of the shorter duration of pain in older patients (20). Older patients may present earlier with TMD symptoms because they have more time to go to the hospital.…”
Section: Figmentioning
confidence: 99%